The First-to-File Principle and the Principle of Good Faith in Disputes Over Well-Known Trademarks for Non-Similar Goods (Case Study: Decision No. 2/Pdt.Sus-HKI/Merek/2023/PN Niaga MDN and Supreme Court Decision No.859K/Pdt.Sus-HKI/2024) - Mohammad Akmal Taris Hakim; Suherman Suherman (NOTARIIL Jurnal Kenotariatan, 2026)
Legal protection for trademarks in Indonesia follows the “first to file” principle, which grants exclusive rights to the party that first registers the trademark. However, the application of this principle cannot be separated from the principle of good faith, which serves as a safeguard to ensure that trademark rights are not obtained through improper means, particularly in the protection of well-known trademarks. This study aims to analyze the legal framework regarding the "first to file" principle and the principle of good faith within the system for protecting well-known trademarks, as well as to analyze the judges’ considerations in the BARCO trademark dispute based on the Commercial Court Decision No. 2/Pdt.Sus-HKI/Merek/2023/PN Niaga Mdn and the Supreme Court Decision No. 859 K/ Pdt.Sus-HKI/2024. This study employs a normative legal method using a statutory approach, a case-based approach, and a conceptual approach. The data used consists of secondary data obtained through literature review and analyzed qualitatively. The results of the study indicate that provisions regarding the “first to file” principle, the principle of good faith, and protection for well-known trademarks are regulated in Law No. 20 of 2016 on Trademarks and Geographical Indications along with its implementing regulations. However, in practice, the application of the “first to file” principle remains more dominant compared to the principle of good faith and protection for well-known trademarks. Judges’ considerations place greater emphasis on the formalities of registration and the classification of goods than on brand reputation and the potential for consumer confusion, resulting in trademark protection that remains largely formalistic in nature.